Analisis Metode Penelitian pada Bidang CSR di Indonesia: Analysis of Research Methods in The Field of CSR In Indonesia - Aprilia Rahmawati; Beltien Hanny Pramasterina; Doddy Setiawan (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The purpose of this study is to give a comprehensive picture about the development of Corporate Social Responsibility in accounting research in Indonesia. In this study, CSR research development was traced through mapping articles published in 14 national accredited journals and 10 international journals which sourced from Emerald, Elsevier, Springer, and Wiley. The sample of this research is 81 articles which examine CSR in Indonesia for the period of 2008-2018. This study classifies articles based on research topic, research method, and the model used by the researchers. The research showed that most of the study about CSR in Indonesia discussed about firm size and profitability (as antecedent variable), firm performance (as consequence variable), and the examination and application of CSR practices in Indonesia This research also showed that analytical method is commonly used as the research method in this topic. Keywords: corporate social responsibility, literature review, firm size, profitability, firm performance, analytical method